Students’ Perception on the Use of Peer Learning in Speaking At Madrasah Aliyah Asy-Syafi’iyah Kendari - Suriani Suriani; Hilaluddin Hanafi; Nurnia Nurnia (Halu Oleo University, 2019)
This study was aimed to investigate the students’ perception on the use of peer learning in speaking at Madrasah Aliyah Asy-Syafi'iyah Kendari. The study was guided by the following objectives: (1) to examine how peer learning applied in speaking, (2) to describe how students perceive the use of peer learning in Speaking, and (3) to investigate how peer learning influences students’ motivation in speaking. Furthermore, the study adopted a descriptive research with 11 participants. The participants of this study were taken in grade eleven from the science class who were registered in the academic year 2018/2019. The data were taken from observation, questionnaire and interview, and they were analyzed qualitatively. The following results were obtained: (1) Dominantly, the students applied peer learning such as pair work, discussion and peer group which students interact, gave correction, solve problems with their peers. (2) The students genuinely perceived that peer learning is good and has positive responses such as to assist them in speaking practice and to assess their speaking performance each other. (3) Peer learning influences students' motivation in confident, feel free and comfortable through group learning and pairs. Additionally, students’ perception on the use of peer learning more influenced by their closest friend in speaking. Thus, peer learning is recommended to be implemented in learning speaking.Keywords:Students’ Perception,Peer Learning, Speaking, Motivation.